Nghiên cứu tổng hợp perovskit LaCr0,5Mn0,5O3 ở nhiệt độ thấp bằng phương pháp đốt cháy gel - Dũng và cộng sự, Nguyễn Xuân (Vietnam Journal of Chemistry, 2014)
Nanosized LaCr0.5Mn0.5O3 perovskite was synthesized with relatively high surface area (15.5 m2/g) at low temperature (650oC) by the combustion method using polyvinyl alcohol (PVA) and corresponding metal nitrates. The influence of factors on formation of perovskite phase was studied. Samples were examined by thermogravimetric and differential thermal analysis (TG-DTA), X-ray diffraction (XRD), FT-IR spectra, field emission scanning electron microscopy (FE-SEM) and BET (Brunaure-Emmet-Teller) measurements.